2015
DOI: 10.1016/j.ibmb.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Annotation and expression analysis of cuticular proteins from the tobacco hornworm, Manduca sexta

Abstract: The insect cuticle is a unique material that covers the exterior of the animal as well as lining the foregut, hindgut, and tracheae. It offers protection from predators and desiccation, defines body shape, and serves as an attachment site for internal organs and muscle. It has demonstrated remarkable variations in hardness, flexibility and elasticity, all the while being light weight, which allows for ease of movement and flight. It is composed primarily of chitin, proteins, catecholamines, and lipids. Proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 53 publications
9
64
0
Order By: Relevance
“…However, there are still some cuticular protein genes with unexpected expression in the tissues not derived from ectoderm such as the goad, Malpighian tubule, and fat body (Figs 5, 6, 7, 8). Similar results were found in other species, such as B. mori 20 and Manduca sexta 39. It has been speculated that these proteins are formed and transported to the cuticle-forming tissues from the internal tissues, or its transcripts of these protein genes originated in the attached trachea that possess the epidermic structure6.…”
Section: Discussionsupporting
confidence: 80%
“…However, there are still some cuticular protein genes with unexpected expression in the tissues not derived from ectoderm such as the goad, Malpighian tubule, and fat body (Figs 5, 6, 7, 8). Similar results were found in other species, such as B. mori 20 and Manduca sexta 39. It has been speculated that these proteins are formed and transported to the cuticle-forming tissues from the internal tissues, or its transcripts of these protein genes originated in the attached trachea that possess the epidermic structure6.…”
Section: Discussionsupporting
confidence: 80%
“…The largest family is CPR with gene numbers ranging from as few as 32 in A. mellifera to as many as 156 in Anopheles gambiae . Astonishingly, 207 CPR genes have now been identified in M. sexta (79 RR-1,124 RR-2, 4 RR-3), indicating extensive gene duplication, thus making M. sexta the insect with the greatest number of CPR genes described to date (Dittmer et al, 2015). In comparison, B. mori has 148 CPR genes (56 RR-1, 93 RR-2, 4 RR-3) (Futahashi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, B. mori has 148 CPR genes (56 RR-1, 93 RR-2, 4 RR-3) (Futahashi et al, 2008). Comparison of the M. sexta and B. mori CPR genes (Dittmer et al, 2015) indicated that the greatest difference was evident with the RR-2 genes, for which only 51 orthologous pairs could be established. However, five orthologous groups could be identified, in which 3–13 M. sexta RR-2 genes (42 in total) were clearly related to 3–6 B. mori RR-2 genes (23 in total), although within these groups the M. sexta genes were more closely related to each other than any one of them was to a B. mori gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations